Transformational Leadership, Work Discipline, and Occupational Health and Safety as Determinants of Employee Performance: Evidence from PT Lintech Duta Pratama, Sumbawa - Beni Haryanto; Aditya Yoga Prasetya (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
ABSTRACT This study examines the effect of transformational leadership, work discipline, and occupational health and safety (OHS) on employee performance at PT Lintech Duta Pratama, Sumbawa Site, West Nusa Tenggara. The research is motivated by a decline in employee performance, reflected in reduced productivity and delays in task completion. A quantitative approach was employed, involving 50 employees selected using a census technique. Data were collected through closed-ended questionnaires and analyzed using SPSS, applying validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, and coefficient of determination (R²). The results reveal that transformational leadership, work discipline, and OHS have a positive and significant impact on employee performance. These findings highlight the importance of effective leadership, strong work discipline, and consistent OHS implementation in improving employee performance and organizational productivity.